All Days 1999
DOI: 10.2118/51940-ms
|View full text |Cite
|
Sign up to set email alerts
|

Scale Up in the Near-Well Region

Abstract: This paper was prepared for presentation at the 1999 SPE Reservoir Simulation Symposium held in Houston, Texas, 14-17 February 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…He introduced a well-driven flow by applying appropriate boundary conditions. Durlofsky et al (2000) proposed an extended local region around the well for the fine scale solution for the near well upscaling as shown in fig. 2.17.…”
Section: Near-well Upscalingmentioning
confidence: 99%
See 1 more Smart Citation
“…He introduced a well-driven flow by applying appropriate boundary conditions. Durlofsky et al (2000) proposed an extended local region around the well for the fine scale solution for the near well upscaling as shown in fig. 2.17.…”
Section: Near-well Upscalingmentioning
confidence: 99%
“…Many researchers (e.g. Ding, 1995;Durlofsky et al 2000;Muggeridge et al 2002;Chen and Wu, 2008) have also shown procedures to estimate well index appropriately.…”
Section: Near-well Upscaling In 3-d Modelsmentioning
confidence: 99%
“…In most cases, the coarse-scale parameters are approximated based on fine-scale parameters and/or some local flow calculations, subjected to generic boundary conditions. Therefore, the performance of these methods often depends on the choice of the local boundary conditions and may not adequately capture the key features of the fine-scale flow behaviour, especially in the near-well region (Durlofsky et al 2000).…”
Section: Approachmentioning
confidence: 99%
“…We argue that, in addition to the computational difficulties, a more fundamental reason for upscaling is that, for a given configuration of wells in a reservoir, there is only a limited degree of freedom in the input/output dynamics of the system [i.e., 13 The assumption of fixed boundary conditions might also lead to a poor capturing of near-well effects on the global flow pattern unless a near-well upscaling technique is added (Ding 1995 andDurlofsky et al 2000).…”
Section: Motivationmentioning
confidence: 99%
“…It was known that for the well-driven flow in the porous media, the standard upscaling methods did not work in the vicinity of the wells [5,13]. In the recent paper [3], Chen and Yue developed a multiscale coarse grid algorithm for solving steady flow problem involving well singularities in heterogeneous porous medium based on the over-sampling multiscale finite element method (MsFEM) [10].…”
Section: Introductionmentioning
confidence: 99%